2016
DOI: 10.1177/0363546515625048
|View full text |Cite|
|
Sign up to set email alerts
|

The Vertical Drop Jump Is a Poor Screening Test for ACL Injuries in Female Elite Soccer and Handball Players

Abstract: Dette er siste tekst-versjon av artikkelen, og den kan inneholde små forskjeller fra forlagets pdf-versjon. Forlagets pdf-versjon finner du på www.sage.com: http://dx.doi.org/10.1177/0363546515625048 This is the final text version of the article, and it may contain minor differences from the journal's pdf version. Background: The evidence linking knee kinematics and kinetics during a vertical drop jump (VDJ) to anterior cruciate ligament (ACL) injury risk is restricted to a single small sample. Still, the VDJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
291
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 258 publications
(308 citation statements)
references
References 73 publications
(125 reference statements)
11
291
4
2
Order By: Relevance
“…Valgus motion is likely controlled by neuromuscular contribution of the entire limb kinetic chain [167]. In contrast with previous findings [57,111], controls in study II had greater knee valgus movement in the frontal plane (measured with DVJ) compared to players with ACLR (median difference of 0.017 m). Current postoperative rehabilitation programs emphasise the importance of landing with toes and knees pointed forward, and minimising knee valgus motion during take-off and landing.…”
Section: Functional Performance After Aclr and Return To Footballcontrasting
confidence: 80%
See 2 more Smart Citations
“…Valgus motion is likely controlled by neuromuscular contribution of the entire limb kinetic chain [167]. In contrast with previous findings [57,111], controls in study II had greater knee valgus movement in the frontal plane (measured with DVJ) compared to players with ACLR (median difference of 0.017 m). Current postoperative rehabilitation programs emphasise the importance of landing with toes and knees pointed forward, and minimising knee valgus motion during take-off and landing.…”
Section: Functional Performance After Aclr and Return To Footballcontrasting
confidence: 80%
“…Previous studies have often used sophisticated laboratory equipment such as the Biodex balance system [167], force plates [48,145,201] and 3D motion analysis [48,57,111]. The tests used in study II may not have been sensitive enough to detect existing between-group differences.…”
Section: Functional Performance After Aclr and Return To Footballmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study [69] collected prospective DVJ data from 708 Norwegian elite female football and handball players and observed 38 non-contact ACL injuries. This has recently been published [70] with 42 non-contact ACL injuries registered and neither KAM, KAA, knee flexion angle and peak GRF predicted ACL injury. The second study involved US military cadets [71], where 117 ACL injuries were observed in males and females from a cohort of 5758 cadets.…”
Section: Recent Level 1 Evidencementioning
confidence: 99%
“…This trend has not been observed in the context of the biomechanical contributors to primary non-contact ACL injury risk. Although, with the publication of new prospective abstracts [69,80] and a large new prospective cohort study [70] more high level of evidence studies are being conducted which is welcome. Yet, additional research efforts are needed.…”
Section: Barriers To Strengthen the Available Evidencementioning
confidence: 99%